TWO ALKYLATED FLAVONOID ISOLATED FROM THE STEM OF THE FERN Chingia sakayensis (Zeiller) Holtt - Suyatno Suyatno; Sri Hidayati Syarief; Nurul Hidajati; Kuniyoshi Shimizu (Indonesian Journal of Chemistry, 2007)
Two known alkylated flavonoid namely matteucinol dan matteucinol-7-O-b-D-glucoside was isolated for the first time from the fern Chingia sakayensis (Zeiller) Holtt's stem. Their structures were elucidated on the basis of spectroscopic evidence and by comparation with those reported data in literature.